Sinergi Kartu Indonesia Pintar dan Bidikmisi Sebagai Motivasi Studi Lanjut Bagi Siswa Sekolah Menengah Atas - Inna Kuswandari; Abulloh Jaelani; Nenik Estuningsih (Jurnal Pemberdayaan Masyarakat, 2022)
This community service activity focused on efforts to increase the motivation and spirit of high school graduates in the Tuban Regency for further studies in higher education. This activity was both online and offline. In the initial stage, students give motivated by the importance of higher education for a better future. Then a potential measurement test was also conducted to obtain an overview of students' motivation and potential for further studies. The next stage is a socialization of the Bidikmisi program and services with the Indonesia Smart Card (ISC) for Lectures and various financing schemes. The results of the potential measurement test showed that students' motivation and fighting power were in the range slightly above average. This shows that students' motivation and fighting power are not yet strong as capital to compete and face challenges when studying. Therefore, students' enthusiasm and motivation need to be improved, and reminded continuously that motivation is an important factor for someone to achieve their dreams. This activity also supports efforts to achieve sustainable development goals (SDGs), namely SDG1: No Poverty, SDG4: Quality Education, and SDG10: Reduced Inequalities.